Decision Model for the Scheduling of Public Investment Projects in a Health Care Service - Oddershede-Herrera, A (Elsevier B.V., 2025)
This project addresses the lack of a structured decision-making method for prioritizing public investment initiatives within a regional Health Service in Chile. The absence of a formal methodology leads to delays in implementing health solutions for citizens and undermines the efficient allocation of public resources. This issue arises from the lack of clearly defined and justified priorities within the organization, which hampers a strategic approach to investment planning. To tackle this challenge, the project proposes the development of a decision-support model for prioritizing and scheduling public investment projects. The model employs the Analytic Hierarchy Process (AHP) to establish a systematic and transparent framework for evaluating and ranking initiatives based on multiple criteria. Once priorities are set, a scheduling algorithm is applied to determine the optimal timing for project implementation within budget constraints. This approach is expected to enhance the rigor, transparency, and efficiency of investment decision-making in public health planning. © 2025 The Authors.